STUDY OF TAOISM ETHICS AND ITS IMPLEMENTATION FOR DEMOCRATIC COMMUNITY DEVELOPMENT IN INDONESIA - Widisuseno, Iriyanto (Faculty of Humanities, Diponegoro University, 2018)
The people of Indonesia are currently entering a period of transition. The transition is when democratic civil society creates opportunities for freedom, openness, and a broader political space of participation from people without exception. Civil society mobility affects the need for law enforcement and respect for moral values. The study of Taoist ethics becomes essential to explore an ethical way of life according to the laws of nature. The way the analysis uses: descriptions of hermeneutics, heuristics and synthesis. To achieve the first research objective using the hermeneutic description method, to reveal the fundamental meaning that gives importance to the ethical teachings of Taoism. The second research objective uses a heuristic approach, a step of finding ways to solve problems scientifically. The road to science, through an explorative understanding of the meaning of concepts or texts, to derive the fundamental problem specifications that arise in the empowerment of democratic civil society in Indonesia. To achieve the third research objective, using the synthesis approach, which is combined exclusively by drawing a node of logical and contextual relevance. The results show that the universal ethical values in Taoist natural ethics such as simplicity, honesty, discipline, compassion, obedience, sincerity, justice, have significance and relevance to the basic issue of plurality of civil society's life to democratic society in Indonesia.